2016
DOI: 10.1242/jcs.186429
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog controls enteric nervous system development by patterning the extracellular matrix

Abstract: The enteric nervous system (ENS) develops from neural crest cells that migrate along the intestine, differentiate into neurons and glia, and pattern into two plexuses within the gut wall. Inductive interactions between epithelium and mesenchyme regulate gut development, but the influence of these interactions on ENS development is unknown. Epithelial-mesenchymal recombinations were constructed using avian hindgut mesenchyme and nonintestinal epithelium from the bursa of Fabricius. These recombinations led to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Regulatory signals from the peripheral nerves have essential roles in the developmental and physiologic process of digestive tract muscles (40,41). Previous studies have reported that Shh overexpression could lead to aganglionosis and that the inhibition of Shh signaling could increase the number of neuronal cells (42,43). However, we did not find obvious differences in the expression of peripheral nerve markers (b3-tubulin and PGP9.5) between the developing esophagi of CK14-Cre; Shh fl/fl mice and those of WT mice, suggesting that epithelial Shh might not affect the development and growth of nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory signals from the peripheral nerves have essential roles in the developmental and physiologic process of digestive tract muscles (40,41). Previous studies have reported that Shh overexpression could lead to aganglionosis and that the inhibition of Shh signaling could increase the number of neuronal cells (42,43). However, we did not find obvious differences in the expression of peripheral nerve markers (b3-tubulin and PGP9.5) between the developing esophagi of CK14-Cre; Shh fl/fl mice and those of WT mice, suggesting that epithelial Shh might not affect the development and growth of nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that regulate ENCC development are incompletely understood, although a growing body of evidence supports the importance of interactions between ENCCs and the gut microenvironment. These include interactions between ENCC surface receptors and ligands present in the mesenchyme (Goldstein et al 2013) and extracellular matrix (ECM) proteins (Akbareian et al 2013;Nagy et al 2016). Like the smooth muscle, blood vessels share a close anatomic relationship with the ENS, and endothelial cells may act as a substrate for guiding and promoting ENCC migration and proliferation (Nagy et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes (except D4-ST) were also required for neuronal polarization (i.e., axon-dendrite polarity) of hippocampal neurons in vitro and cortical neurons in vivo (Nishimura et al, 2010). Additional CS-dependent processes include interactions of CS with Sonic Hedgehog (Shh) during development of the enteric nervous system in chicks (Nagy et al, 2016), Semaphorin 3A dependent repulsion of cortical neurons in the telencephalon (Zimmer et al, 2010), and an inhibitory role in axonal collateral branching (Sainath et al, 2017). In addition, ErbB1 (Koprivica et al, 2005) is involved in regulating the CS-dependent inhibition of neurite growth in dorsal root ganglion axons in vitro.…”
Section: Cs/ds In Neuronal Patterningmentioning
confidence: 99%